Predicted loading on the menisci during gait: The effect of horn laxity. Issue 8 (1st June 2015) - Guess, Trent M.; Razu, Swithin; Jahandar, Hamidreza; Stylianou, Antonis
Abstract: Radiographic measurements have established a link between meniscus extrusion and meniscus degeneration as well as with knee osteoarthritis. The presented work combines medical imaging with motion capture data from two healthy female subjects to create subject specific knee models that predict tibio-menisco-femoral contact forces and ligament forces during muscle driven simulations of barefoot gait. The developed computational models were used to explore the relationship between the extent of meniscal extrusion and biomechanical function by altering the laxity of the meniscal horn attachments during gait. The extrusion distance increased as laxity increased and the amount of contact force transferred through the menisci during gait decreased rapidly as the meniscal attachments became more lax. Horn attachment lengths that were 20% longer than MRI attachment lengths resulted in an almost complete loss of force transfer through the menisci during the gait cycle. Relatively small changes (2–3 mm) in the lengths at which horn bundles first become taut, manifested in large changes in the capacity of the tissue to transmit forces. As meniscal horn attachment laxity increased from 80% to 120% of the MRI measured horn distance, medial meniscus extrusion increased 3.9 mm for the first subject and 2.7 mm for the second subject. For the same horn laxity changes, the percent of medial tibiofemoral contact force transmitted through the medial meniscus during early stance decreased from 51% to 8% and from 36% to 14% for the two subjects. The results of our study show that increased meniscal extrusion occurs with increased laxity of the meniscal tibia attachments and this increased laxity results in loss of meniscal function.